Inovasi Penyiraman Bibit Pinus Berbasis Kelembaban Tanah Menggunakan Microcontroller Berbasis Arduino Untuk Meminimalisir Kematian Bibit (Studi Kasus PT.XYZ) - Setya Putra, Danang; Yusianto, Rindra (Universitas Kadiri, 2025)
Irregular watering at the nursery stage is often the cause of death of Pinus merkusii seedlings. This study aims to design and test an Arduino-based automatic watering system with a soil moisture sensor to maintain optimal humidity in the polybag planting medium of pine seedlings. The study was conducted through an experimental method with direct testing using seedling samples. The system is designed to activate the water pump when soil moisture drops below 60% and stop watering when humidity reaches 70%, with real-time monitoring via sensors. Humidity data was taken every 1 hour for 10 hours of testing. The test results showed that the system was able to maintain soil moisture within the ideal range, provide the right watering response, and was effective in reducing the burden of labor. The recommendation from this study is the development of a system using Arduino as a controller to optimize seedling watering more efficiently, evenly, and measurably in order to minimize seedling mortality.